2014
DOI: 10.5152/tud.2013.030
|View full text |Cite
|
Sign up to set email alerts
|

Ureterocutaneostomy: for whom and when?

Abstract: Objective: To discuss the indications and the results of the patients treated with ureterocutaneostomy (UCN) for urinary diversion in our center. Material and methods:Between March 2008 and November 2012, 27 patients (19 males and 8 females) were treated with UCN in our clinic. Patients' ages ranged between 56-78 years. Radical cystectomy was performed on 21 of these patients. The patients underwent transureteroureterostomy and UCN or unilateral or bilateral side-by-side UCN on the abdominal wall. Double-J ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
4

Year Published

2015
2015
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 23 publications
1
13
0
4
Order By: Relevance
“…Being relatively easy to perform and having a low risk of complications makes UCS a first-line choice, especially for patients with multiple comorbidities. Kozacıoğlu et al (12) reported that important comorbidities such as hypertension, chronic obstructive pulmonary disease, and diabetes were common among the patients in their study. We found that UCS was most commonly performed on high-risk patients with major comorbidities, and for this reason the operation was done under a combination of spinal and epidural anesthesia in 66.6% of patients.…”
Section: Discussionmentioning
confidence: 88%
“…Being relatively easy to perform and having a low risk of complications makes UCS a first-line choice, especially for patients with multiple comorbidities. Kozacıoğlu et al (12) reported that important comorbidities such as hypertension, chronic obstructive pulmonary disease, and diabetes were common among the patients in their study. We found that UCS was most commonly performed on high-risk patients with major comorbidities, and for this reason the operation was done under a combination of spinal and epidural anesthesia in 66.6% of patients.…”
Section: Discussionmentioning
confidence: 88%
“…The median time elapsed between DJS removal and stoma stenosis diagnosis was 3 (1-12) weeks and the follow-up of these patients continued with ureteral stents replaced at regular intervals. The median stent replacement interval in these patients was 14 weeks (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). During the follow-up, the number of patients requiring permanent dialysis due to postrenal ARF was 5 (6%).…”
Section: Resultsmentioning
confidence: 99%
“…The stricture development rate may be higher than 50% in some studies. It has been reported that palliative diversion was best initially attempted with indwelling ureteral stents because of this complication (12,13,14). In their study published in 2016, Hatakeyama et al (15) compared three different diversion methods (UC, IC, and neobladder).…”
Section: Discussionmentioning
confidence: 99%
“…16 Диагностика и лечение опухолей мочеполовой системы. Рак мочевого пузыря осложнений и избавляют пациентов от билатеральной уростомы [20][21][22]. С другой стороны, имеются исследования, результаты которых показывают, что пациенты группы высокого анестезиологического риска имеют более распространенные опухоли мочевого пузыря и в 2 раза выше вероятность летального исхода после выполнения радикальной цистэктомии [23].…”
Section: Introductionunclassified